The EU legislation on the supervision of activities of economic operators: substance of procedural rights and impact on Lithuanian law - Šilvaitė, Eimantė (Vilnius University Open Series, 2020)
This article discusses the EU legislation, regarding main procedural rights of economic operators applied in the supervision procedure of their activities and its impact on supervisory procedures in Lithuania, as well as the institute of supervision of activities of economic operators in Lithuania and regulation of main procedural rights granted to economic operators. By analysing the EU primary, secondary and Lithuanian (national) legislation, as well as the case law of European and Lithuanian judicial authorities, the insights into future challenges for both the EU and Lithuanian law are provided. It is being claimed that the EU is moving towards codification and strengthening of procedural rights, which inevitably influences Lithuanian legal system and the protection of individuals, inter alia legal persons.